Lamellar Cataract - Pavani Murthy Penugondla; Srinivasa S. Sastry; Sreenivasa P. Rao (Delhi Journal of Ophthalmology)
A 38-year-old male presented with complaints of decreased vision since childhood, which has been increasing in the past decade. Examination revealed a central lamellar cataract in both the eyes.